2016
DOI: 10.1016/j.mimet.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics for effective concentration and sorting of waterborne protozoan pathogens

Abstract: We report on an inertial focussing based microfluidics technology for concentrating waterborne protozoa, achieving a 96% recovery rate of Cryptosporidium parvum and 86% for Giardia lamblia at a throughput (mL/min) capable of replacing centrifugation. The approach can easily be extended to other parasites and also bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Although conventional PCR and BAX V R System PCR assays allow for Salmonella detection in hours, steps preceding PCR may add days. 13,14 Multiple reports showed that foods could be filtered through membranes in quantities useful for conventional detection procedures (such as plating), [18][19][20] although crossflow microfiltration or ultrafiltration of cells and proteins resulted in fouling of the membrane and limited the volume of sample that could be processed. [21][22][23][24][25][26] We showed that endopeptidase treatment followed by hollow fiber microfiltration was effective in overcoming fouling of the hollow fiber membrane, while avoiding loss of viability of the Salmonella cells.…”
Section: Accelerated Sample Preparationmentioning
confidence: 99%
“…Although conventional PCR and BAX V R System PCR assays allow for Salmonella detection in hours, steps preceding PCR may add days. 13,14 Multiple reports showed that foods could be filtered through membranes in quantities useful for conventional detection procedures (such as plating), [18][19][20] although crossflow microfiltration or ultrafiltration of cells and proteins resulted in fouling of the membrane and limited the volume of sample that could be processed. [21][22][23][24][25][26] We showed that endopeptidase treatment followed by hollow fiber microfiltration was effective in overcoming fouling of the hollow fiber membrane, while avoiding loss of viability of the Salmonella cells.…”
Section: Accelerated Sample Preparationmentioning
confidence: 99%
“…18,19 Most of the effort in this field is focused on the control of solid particles with diameters smaller than the size of the channel; typically, by one order of magnitude. [20][21][22][23][24][25][26][27][28][29][30] Although there are similarities between the behavior of rigid particles and bubbles, deformation of the bubbles [31][32][33][34] complicates the understanding of the physical phenomena evidenced in gas/liquid flows. Understanding the active forces affecting bubble motion is necessary in order to explain its behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The source of this fragmentation is most likely high shear forces within the pump and it is recommended to use a progressing cavity pump to mitigate this issue. It can be noted that for smaller inertial focusing channels with similar profile heights (30 and 50 μm high), 100% recoveries have been reported in previous works where syringe pumps have been used293037. However, such pumps cannot be used for recirculating continuously the sample.…”
Section: Resultsmentioning
confidence: 71%
“…For example in environmental monitoring for pathogens such as Cryptosporidium , 1000 L is filtered282930. Other examples include algal dewatering for biofuel production3132, to clean circulating oil in vehicles and heavy rotating machinery33 and bioprocessing/biotechnology34.…”
mentioning
confidence: 99%